2017
DOI: 10.3389/fmicb.2017.01280
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pelagic Iron-Oxidizing Zetaproteobacteria from the Chesapeake Bay Oxic–Anoxic Transition Zone

Abstract: Chemolithotrophic iron-oxidizing bacteria (FeOB) could theoretically inhabit any environment where Fe(II) and O2 (or nitrate) coexist. Until recently, marine Fe-oxidizing Zetaproteobacteria had primarily been observed in benthic and subsurface settings, but not redox-stratified water columns. This may be due to the challenges that a pelagic lifestyle would pose for Zetaproteobacteria, given low Fe(II) concentrations in modern marine waters and the possibility that Fe oxyhydroxide biominerals could cause cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 85 publications
2
78
0
Order By: Relevance
“…The distribution of Fe revealed by BSE‐SEM (Figure c–h) demonstrates that these textural features are composed of silicified twisted stalks. While some Fe‐oxidizing species are known to form dendrite‐like extracellular structures (Chiu, Kato, McAllister, Field, & Chan, ; Edwards, Rogers, Wirsen, & McCollom, ), dendritic growth of stalks produced by Mariprofundus ferrooxydans or other benthic Zetaproteobacteria has not previously been reported. Twisted stalks have been discovered in association with Frutexites ‐like iron shrubs in biofilms with active Fe and N‐cycling, but were not found to constitute the main framework of these dendrites (Heim, Quéric, Ionescu, Schäfer, & Reitner, ).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of Fe revealed by BSE‐SEM (Figure c–h) demonstrates that these textural features are composed of silicified twisted stalks. While some Fe‐oxidizing species are known to form dendrite‐like extracellular structures (Chiu, Kato, McAllister, Field, & Chan, ; Edwards, Rogers, Wirsen, & McCollom, ), dendritic growth of stalks produced by Mariprofundus ferrooxydans or other benthic Zetaproteobacteria has not previously been reported. Twisted stalks have been discovered in association with Frutexites ‐like iron shrubs in biofilms with active Fe and N‐cycling, but were not found to constitute the main framework of these dendrites (Heim, Quéric, Ionescu, Schäfer, & Reitner, ).…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms that oxidize Fe(II) and reduce Fe(III) have been reported from various Fe‐rich environments (>1 wt % Fe) such as hot springs (Kasama and Murakami, ), ferrous hydrothermal vents (Emerson and Moyer, ; Edwards et al ., ; Fitzsimmons et al ., ), Fe seeps and springs (Blöthe and Roden, ; Hegler et al ., ), rice paddy soils (Li et al ., ; Peng et al ., ), salt lake sediment (Emmerich et al ., ), microbial mats in the arctic tundra and in close proximity of hydrothermal vents (Emerson et al ., ) and ponds (Bruun et al ., ). In contrast, iron‐poor environments (with relatively low, i.e., micromolar, concentrations of Fe(II)) remained relatively unexplored, however, very recently, microbial Fe‐cycling has also been described for environments with low Fe content (Laufer et al ., ; Chiu et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…With this experiment, we have shown that PV-1 outpaces abiotic oxidation below 49 μM O 2 , and accounts for up to 99% of the Fe oxidation at 10 μM O 2 (Figure 1; Table 3). In cultures of M. aestuarium CP-5 and M. ferrinatatus CP-8, oxygen concentrations ranged from 0.07-2.0 μM O 2 within the cell growth band (25). This range of O 2 growth conditions is well below the level at which almost all Fe oxidation was biotic for PV-1, suggesting that many Zetaproteobacteria are well adapted to compete and thrive under micromolar and submicromolar O 2 concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…While most Zetaproteobacteria isolates form a stalk, some make other biomineral morphologies (Table 1; Figure 3A). Mariprofundus ferrinatatus CP-8 and M. aestuarium CP-5 form shorter filaments that resemble the dreadlock hairstyle (Figure 3C) (25). Dreads were originally observed in terrestrial FeOB Gallionellaceae Ferriphaselus spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation